HUMANISTIC RIGHTS, CHALLENGES AND ISSUES OF ISLAMIC MODERATION UNDER MINISTER OF RELIGIOUS AFFAIRS GUS YAQUT - Zakiah, Sitti; Rif’atul Islam, Naila; Haslindah; Ali Halidin; Aidasari (Institut Agama Islam Negeri Bone, 2025)
There were six advantages of Gus Yaqout when he served as Minister of Religion in the era of President Jokowi. These six of superior programs also regulated the lifestyle of religious communities based on moderation, namely; The first; Revitalization of KUA Services (District Office of Religious Affairs ): KUA is seen as the front guard of Ministry of Religion services. KUA should become a service center for all religions, so that it is more global, universal and transparent and does not give suspicion to the other religions. Secondly; Islamic Boarding School Independence: Program to strengthen the potential empowerment of Islamic boarding schools, especially in the field of entrepreneurship so that they can fulfill their own needs, and The third; Digital Transformation: Digitalization of public services, including the development of integrated the applications such as Superapps Pusaka and the construction of a data center for one Ministry of Religion data. The fourth; Cyber Islamic University: This initiative aims to develop technology-based Islamic higher education, no longer towards a World Class University, but into an Islamic World Destination University, this is after the establishment of UIII in Depok and UIN Cyber Nurjati Cirebon. The fifth; Religiosity Index: Development of the World Islamic Destination University, this index is to measure the level of religiousness of society. All of Gus Yaqout's programs are based on the nawacita of strengthening religious moderation to create the harmony between religious communities in Indonesia. This includes strengthening moderate religious views, attitudes and practices.